2013
DOI: 10.5489/cuaj.1390
|View full text |Cite
|
Sign up to set email alerts
|

Massive rectal bleeding after prostate biopsy controlled by endoclipping in a patient using ASA

Abstract: A case of severe rectal bleeding following transurethral ultrasound (TRUS)-guided prostate biopsy is reported. Rectal bleeding is considered a minor, transient complication of this standard diagnostic procedure that can usually be controlled successfully by conservative measures. In this case where the patient had been taking acetylsalicylic acid (ASA), massive bleeding required hospitalization and blood transfusions. Conservative treatment attempts were not succesful, and profuse rectal bleeding was eventuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There is only one case report of a life-threatening rectal bleeding complication in a patient taking ASA. However, that was only one case among 136 patients (0.7%) on ASA, and the causality was not clear 11 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is only one case report of a life-threatening rectal bleeding complication in a patient taking ASA. However, that was only one case among 136 patients (0.7%) on ASA, and the causality was not clear 11 …”
Section: Discussionmentioning
confidence: 93%
“…There are some reports about prostate biopsy in patients continuing AP or AC 6, 7, 8, 9, 10, 11. Almost all reports showed that although continuation of AAs before prostate biopsy increased the frequency of minor bleeding complications or prolonged the duration of self-limited hematuria or rectal bleeding, it did not increase severe hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have been published regarding patients who required aggressive treatment, including blood transfusion, because of late-onset massive rectal bleeding. 2 , 3 , 4 Recently, several risk factors for rectal bleeding have been suggested, such as increasing biopsy core numbers, advanced age, poorly controlled hypertension, and constipation, whereas the influence of antiplatelets remains controversial. 2 Because these risk factors would increase according to the age of patients and the expansion of prostate biopsy indications, a risk of severe rectal bleeding should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, colorectal endoscopy is chosen when conservative treatment for managing severe rectal bleeding fails. 2 , 3 The advantages of colorectal endoscopy are as follows: it can pinpoint the bleeding site and provide an expanded view; it can achieve hemostasis (after pinpointing the bleeding site) immediately using epinephrine injection, clipping, or banding; it can be performed without anesthesia and using antiplatelet or anticoagulation medications. Therefore, colorectal endoscopy is safe and effective in arresting severe rectal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, life-threatening rectal hemorrhage can occur following a TRUS-guided prostate biopsy. In our review of the literature, we found a total of 15 reported cases of a rectal hemorrhage requiring red cell transfusion ( Table 1 ) [ 8 9 10 11 12 13 14 15 16 17 ]. Two of the cases were ultimately managed using a rectal balloon tamponade.…”
Section: Discussionmentioning
confidence: 99%